Pengabdian Kepada Masyarakat Dalam Peningkatan Infrastruktur Jalan Desa Pakuwon - Madi Hermadi; Muhammad Rizal Fahlevi Sonaris; Alefti Rico Januarsa; Muhamad Fathan Fadillah; Regi Al Fatah; Hopipah; Athaya Zhafirah; Silvia Nur Hakim; Rafi Algifari; Ilham Nurdiansah; Siti Rahmawati; Wanda Laela Zahra; Saepul Sa Ban; Ramdhani Sulaeman Burhanudin; Mohamad Kayla Putra Anasa; Muhamad Yakfi Asiddiki; Miftahul Taopik; Ai Sena Marlina (Institut Teknologi Garut, 2026)
Village roads are an important infrastructure that supports the social, economic, and educational activities of the community. Some sections of the roads in Pakuwon Village, Cisurupan District, Garut Regency, have been damaged by potholes and uneven surfaces, hindering the mobility of residents and potentially reducing the safety of road users. This community service activity aims to improve the quality of village road infrastructure through community-based road repairs. The implementation method uses a participatory approach in the Real Work Lecture program by involving students, village governments, and local communities in the planning, implementation, and evaluation stages of the activity. Repairs were carried out on a 400-meter section of road through road patching activities using materials that were available independently and support from partners. The results of the activity showed an improvement in the physical condition of the road, which was now smoother, safer, and more comfortable to travel on. In addition to the physical impact, this activity also encouraged increased community participation and awareness of village infrastructure maintenance. For students, this activity provided direct learning experiences in the application of knowledge and strengthened their role as agents of change in the community. Thus, this community service activity provided dual benefits, both for the village community and for the development of student competencies.